VARIOUS NON-SURGICAL THERAPY IN CARPAL TUNNEL SYNDROME THAT CAN BE AN OPTIONAL THERAPY FOR DENTISTS: SCOPING REVIEW - Brigitta, Brigitta; Anggraini, Wita; Sulistyowati, Indrani; Ariyani, Annisaa Putri; Holil, Levana (Universitas Baiturrahmah, 2024)
Introduction: Carpal tunnel syndrome (CTS) is a common condition among dentists due to awkward hand positions, repetitive hand movements, mechanical pressure on the palms, strong grips, and vibration of tools involved in their work. Non-surgical therapy is recommended for mild to moderate levels of CTS, while surgical treatment may be considered for severe cases. Aim: This study aims to determine the effectiveness of various non-surgical therapy for CTS. Method: The literature search used Boolean language in PCC format on PubMed and Google Scholar databases. The literature search was according to PRISMA-ScR flow chart guidelines and 6,641 articles were obtained. 16 articles met the inclusion criteria, consisting of: splinting (n=2), local steroid injection (n=2), median nerve neuromobilisation (n=2), and journals that tested and compared a combination of non-surgical therapies or more than one non-surgical therapy (n=10). Result: This review shows that non-surgical therapies are effective for CTS patients. Conclusion: Various non-surgical treatment for CTS is effective in reducing pain and improving hand functional ability. These therapies can be an optional therapy for dentists with high CTS risk factors.